Green Human Resource Management, Financial Markets and Pollution Nexus in Saudi Arabia - Alkhateeb, Tarek Tawfik Yousef; Alkahtani, Nasser Saad; Mahmood, Haider (International Journal of Energy Economics and Policy, 2018)
Financial markets play an important role in accelerating the economic activities in any country but it may also harm environment if financial funds are invested in the project which are environment friendly. Further, Green Human Resource Management (GHRM) may help in reducing Co2 emissions. This paper examines the influences of Financial Market Development (FMD) and GHRM on the pollution of Saudi Arabia. We explore this by using cointegration on time-series of 1971-2016. Results of this study corroborate that FMD and Economic Growth (EG) are positively contributing in CO2 emissions and GHRM is helping in reducing. We recommend the financial sector to provide concessional loans to the projects which are using clean energy technology and GHRM needs attention to support clean environment. Keywords: Financial Market Development; Co2 Emissions; Economic Growth JEL Classifications: D53; Q53; O47